An orally bioavailable broad-spectrum antiviral inhibits SARS-CoV-2 in human airway epithelial cell cultures and multiple coronaviruses in mice - Sheahan, Timothy P; Sims, Amy C; Zhou, Shuntai; Graham, Rachel L; Pruijssers, Andrea J; Agostini, Maria L; Leist, Sarah R; Schäfer, Alexandra; Dinnon, 3rd, Kenneth H; Stevens, Laura J; Chappell, James D; Lu, Xiaotao; et al. (Science translational medicine, 2020)
Coronaviruses (CoVs) traffic frequently between species resulting in novel disease outbreaks, most recently exemplified by the newly emerged SARS-CoV-2, the causative agent of COVID-19. Here, we show that the ribonucleoside analog β-d-N -hydroxycytidine (NHC; EIDD-1931) has broad-spectrum antiviral activity against SARS-CoV-2, MERS-CoV, SARS-CoV, and related zoonotic group 2b or 2c bat-CoVs, as well as increased potency against a CoV bearing resistance mutations to the nucleoside analog inhibitor remdesivir. In mice infected with SARS-CoV or MERS-CoV, both prophylactic and therapeutic administration of EIDD-2801, an orally bioavailable NHC prodrug (β-d-N -hydroxycytidine-5'-isopropyl ester), improved pulmonary function and reduced virus titer and body weight loss. Decreased MERS-CoV yields in vitro and in vivo were associated with increased transition mutation frequency in viral, but not host cell RNA, supporting a mechanism of lethal mutagenesis in CoV. The potency of NHC/EIDD-2801 against multiple CoVs and oral bioavailability highlights its potential utility as an effective antiviral against SARS-CoV-2 and other future zoonotic CoVs.